Maxillary posterior intrusion with corticotomy-assisted approaches with zygomatic anchorage-a finite element stress analysis - Cemile Uysal; Burcu Baloş Tuncer; Cumhur Tuncer (SpringerOpen, 2019)
Abstract Background Anterior open bite is one of the most difficult malocclusions to treat and maintain in orthodontics. An effective treatment approach to correct anterior open bite is the intrusion of maxillary posterior teeth. The aim of this study was to evaluate the effects of corticotomy-assisted posterior maxillary intrusion with zygomatic anchorage by using finite element stress analysis. Methods An acrylic bite block on the posterior teeth including two transpalatal arches were modeled and 1.96 N intrusive force was loaded. Three scenarios were set, first with no subapical corticotomy, second with buccal, and third with both buccal and palatal corticotomies. The stress distributions along the cortical, cancellous bone surfaces, and dental structures were assessed by finite element stress analysis. Results Stress distributions over cortical and cancellous bones were commonly located at the inferior curvature of the zygomatic buttress area and posterior teeth for all scenarios. Stress values above the apices of anchor teeth were decreased for both corticotomy scenarios. Increased stress distributions were observed in cancellous bone around corticotomy regions. Despite the acrylic appliance and transpalatal arches, the stresses along the posterior teeth were not uniform. The apical third of the first molar mesiobuccal apex showed the highest stress values in all scenarios. Conclusions Corticotomy-assistance effected biomechanical responses of dentoalveolar structures during maxillary posterior intrusion. There was no apparent difference for the stress levels of the root apices between corticotomy scenarios, pointing out that only buccal corticotomy may be a better option in corticotomy-assisted maxillary intrusion.